Medical quiz physiology - D'Souza, Urban (Universiti Malaysia Sabah, 2008)
This book provides a base of medical, dental, allied health and nursing students with zeal and enthusiasm for learning physiology more competitively. The book covers all the systems of physiology with simple questions and answers.